Efficacy of Yoga therapy management in Respiratory disorders - Negi, Chhaya; Bhatia, Mohit; R Pedhekar, Sunanda (Journal of Neonatal Surgery, 2025)
Introduction: Numerous studies have examined the impact of yoga therapy in the management of respiratory disorders, specifically Bronchial Asthma and Chronic Obstructive Pulmonary Disease (COPD). However, these studies exhibit significant variability in sample sizes and methodologies, resulting in inconclusive findings. Therefore, the present study aims to conduct a systematic review to evaluate the efficacy of yoga therapy in the management of respiratory disorders, thereby providing clearer insights into its potential benefits. Methods: A comprehensive search was conducted across several prominent databases, including PubMed, EMBASE, the Cochrane Library, Google Scholar, and ClinicalTrials.gov, to identify relevant studies. These databases were searched using the keywords yoga and pulmonary function. All the potential studies were included based on Prisma guidelines. The primary outcomes of interest included forced expiratory volume in one second (FEV1), forced vital capacity (FVC), peak expiratory flow rate (PEFR), and the percentage of FEV1, FVC, and PEFR relative to predicted values (% pred). Additionally, we examined secondary outcomes such as the 6-minute walking distance (6 MWD). To evaluate effect sizes, we calculated weighted mean differences (WMDs) along with 95% confidence intervals (CIs). Results: In a comprehensive analysis of five randomized controlled trials (RCTs) involving a total of 233 participants, it was found that yoga therapy notably enhanced respiratory health. Specifically, there was a remarkable improvement in Forced Expiratory Volume in 1 second (FEV1), which increased by an average of 123.57 mL (with a 95% confidence interval of 4.12 to 243, P=0.04). The percentage of FEV1 compared to predicted values also saw a significant boost, averaging an increase of 3.90% (95% CI: 2.27 to 5.54, P<0.00001). The results indicated that yoga intervention (YI) significantly improved FVC% (WMD: 3.03 L, 95 % CI: 1.71, 4.35, P < 0.00001), FEV1 (WMD: 0.47 L, 95 % CI: 0.43, 0.51, P < 0.00001), and FEV1% (WMD: 5.74 L, 95 % CI: 4.47, 7.01, P < 0.00001) when compared to control groups. However, no significant effect was observed on FVC (WMD: 0.23 L, CI: 0.16, 0.62. P = 0.25), PEFR (WMD: 0.49, CI: 0.70, 1.67, P = 0.42), MVV (WMD: 9.01, CI: 3.92, 21.94, P = 0.17), and FEV1/FVC (WMD: 3.17, CI: 1.15, 7.48, P = 0.15) as a result of YI. Furthermore, participants demonstrated a notable improvement in their 6-minute walk distance (6 MWD), with an average gain of 38.84 meters (95% CI: 15.52 to 62.16, P=0.001). Conclusions: The existing evidence indicates that yoga therapy may significantly enhance lung function and boost exercise capacity, making it a promising complementary approach for individuals coping with respiratory conditions such as bronchial asthma and chronic obstructive pulmonary disease (COPD). While these initial findings are encouraging, further research is essential to validate our preliminary observations and to explore the enduring benefits of long-term yoga practice on respiratory health..